The angiotensin converting enzyme I/D polymorphism in long distance runners - Hruskovicova, H.; Dzurenkova, D.; Selingerova, M.; Bohus, B.; Timkanicova, B.; Kovacs L. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: There is an assumption that ACE I/D polymorphism represents one of the possible genetic factors that might be associated with sports excellence. Recent studies have identified an increased frequency of I allele in elite endurance athletes, long distance runners, rowers and mountaineers. The aim of this study was to test the hypothesis that the ACE I/D polymorphism is associated with enhanced endurance performance. Methods: We examined this hypothesis by determining ACE I/D allele frequency in 215 marathon runners, 222 half-marathon runners and 18 inline skaters classified by performance (marathon competition results). ACE genotype and allele frequencies were compared with 252 healthy controls. Results: ACE genotype frequency in the whole cohort did not differ from that in the sedentary controls (P<0.56). However, there was an increase of the I/I genotype incidence amongst successful marathon runners scoring on places from 1st to 150th (P<0.01). These findings were confirmed in the group of inline skaters, similarly demonstrating an increase of the I/I genotype (P<0.01). There was no association found between half marathon runners and the ACE genotype (P<0.59). Conclusions: An excess of the I allele in long distance runners confirms the association between the ACE I/D polymorphism and endurance sports performance.